2017
DOI: 10.2174/1874844901704010011
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Progesterone-dependent Signalization

Abstract: Background:Various effects of steroid hormone activity cannot easily be explained by the action of classical nuclear receptors and genomic signal transduction pathways. These activities are manifested principally as rapid processes, lasting from seconds to minutes, resulting in changes in ion transduction, calcium intracellular concentration, and level of the second messengers, which cannot be realized through the genomic pathway. Hence, it has been proposed that other kinds of mediators should be involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, PGRMC1-depleted cells exhibited apoptotic phenotype when treated with progesterone, 39 suggesting a potential role of this receptor as a marker for neoplasia. 40 Little is known about the PGRMC1 function in insulin producing cells, as well as and in pregnancy and gestational diabetes scenario, but it has been shown that this receptor is expressed in human placenta, primarily in syncytiotrophoblasts, smooth muscle cells of the placental vasculature, and in villous capillaries during the pregnancy. 41 The function of PGRMC1 in preterm delivery prevention by progesterone treatment has been also studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PGRMC1-depleted cells exhibited apoptotic phenotype when treated with progesterone, 39 suggesting a potential role of this receptor as a marker for neoplasia. 40 Little is known about the PGRMC1 function in insulin producing cells, as well as and in pregnancy and gestational diabetes scenario, but it has been shown that this receptor is expressed in human placenta, primarily in syncytiotrophoblasts, smooth muscle cells of the placental vasculature, and in villous capillaries during the pregnancy. 41 The function of PGRMC1 in preterm delivery prevention by progesterone treatment has been also studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PGRMC1-depleted cells exhibited apoptotic phenotype when treated with progesterone (158), suggesting a potential role of this receptor as a marker for neoplasia (159).…”
Section: Discussionmentioning
confidence: 99%